Valsartan in Combination with Tripterygium Glycosides Protects against Chronic Nephritis via the Toll-Like Receptor 4 Pathway - Jiabao Dong; Duo Huang; Ling Jing; Mengmeng Wu (Analytical Cellular Pathology)
Objective. Valsartan has been studied to exert effects on kidney disease. However, the concrete function of valsartan in combination with tripterygium glycosides in chronic nephritis remained largely unknown. The study was designed to unravel the impacts of valsartan and tripterygium glycosides in chronic nephritis through the Toll-like Receptor 4 (TLR4) pathway. Methods. The renal function indicators such as serum creatinine (Scr), blood urea nitrogen (BUN) and β2 microglobulin (β2-MG), 24 h urine protein (Upro) levels, and blood lipid indicators such as total cholesterol (TC), low-density lipoprotein (LDL-C), triacylglycerol (TG) and high-density lipoprotein (HDL-C), inflammatory factors (e.g., IL-1β and IL-8), and the proportion of T lymphocyte subpopulations (CD4+ and CD8+) were detected in chronic nephritis patients before and after treatment with valsartan alone or valsartan combined with tripterygium glycosides. Symptoms of adverse reactions were recorded. TLR4 expression in the patients’ serum was examined. Results. Compared to patients before treatment, after treatment with valsartan alone or valsartan combined with tripterygium glycosides, the renal function indicators Scr, BUN, and 24 h levels were reduced, and TC, TG, and LDL-C levels were reduced, while HDL-C levels were elevated; inflammatory responses (IL-1β and IL-8) were mitigated; CD4+ ratio and CD4+/CD8+ ratio increased yet CD8+ ratio decreased; TLR4 expression was silenced after treatment. All of the changes were more obvious in patients after being treated with valsartan combined with tripterygium glycosides. Conclusion. Valsartan in combination with tripterygium glycosides protects against chronic nephritis via suppressing the Toll-like Receptor 4 pathway.